2020
DOI: 10.1109/oajpe.2019.2952804
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Residential Water Heaters for Peak Shifting and Frequency Response Services

Abstract: The increased penetration of renewable energy resources poses challenges for grid stability. The stochastic generation of solar and wind power cannot be controlled to follow load. And, the transition away from synchronous generators is reducing the capacity to arrest and recover from frequency disturbances. Smart electric water heaters provide utilities with an appliance that can be remotely controlled and serve as a form of energy storage. They have very fast response times and make up a large amount of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…In previous research, EWHs were used to regulate the frequency in an electric power distribution system [30]. Another research study showed that the aggregated EWH load can be controlled to contribute to shifting the system peak load [31]. Communities with large penetration of controllable EWH have, in principle, the potential for providing ancillary services.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, EWHs were used to regulate the frequency in an electric power distribution system [30]. Another research study showed that the aggregated EWH load can be controlled to contribute to shifting the system peak load [31]. Communities with large penetration of controllable EWH have, in principle, the potential for providing ancillary services.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this work, all devices are assumed to operate with unity power factor, a reasonable assumption for power electronic-interfaced devices (such as EV chargers) or resistive immersion heaters. The aggregator would take responsibility for ensuring suitable availability and response from the fleet of devices [7], [18].…”
Section: B Indices For Evaluating Risk Of Violationsmentioning
confidence: 99%
“…To estimate the values of both the ECVV and the LoVV, we use a 'plug-in estimator' [33,Ch. 8], estimating the values of these indices by sampling from (4) and then calculating estimates directly from the load flow solutions from ( 5), (7). Estimated ζ % SHC values are found by linear interpolation from the estimated LoVV.…”
Section: B Indices For Evaluating Risk Of Violationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the capacity, the residential loads account for a significant proportion among all the candidates [8] - [10]. Through proper control strategy, electric water heater (EWH) [11], heating, ventilation, and air conditioning (HVAC) [12] can be aggregated to provide frequency regulation services.…”
Section: Introductionmentioning
confidence: 99%